Context-aware services for physical hypermedia applications - Rossi, Gustavo Héctor; Challiol, Cecilia; Gordillo, Silvia Ethel; Fortier, Andrés (2006)
In this paper we present an approach for designing and deploying context-aware services in the context of physical hypermedia applications, those applications in which mobile users explore real and digital objects using the hypermedia paradigm. We show how to adapt the objects’ response to the user’s navigation context by changing the role these objects play in the user’s travel. We first motivate our research with a simple example and survey some related work; next we introduce the concept of travel object and show that physical objects might assume the role of different type of travel objects. We then present an architectural approach for context-aware services and describe its evolution into a software substrate for physical hypermedia services. We conclude by indicating some further work we are pursuing.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
Proceedings of CAMS 2006. International Workshop on Context-Aware Mobile Systems, Springer LNCS, 2006, October.
Keywords: SERVICIOS BASADOS EN LOCALIZACIÓN; APLICACIONES SENSIBLES AL CONTEXTO; ARQUITECTURAS DE DOMINIO ESPECÍFICO; ORIENTACIÓN A OBJETOS; HIPERMEDIA FÍSICA